The Relationship Between Body Composition and 12 Minute Run Test Among Cadet Medical Students in The Undergraduate Medical Program Republic of Indonesia Defense University - Disty Chania; grace corlesa; roby syah putra firmansyah; markus wibowo; nirawan putranto; justin ibnu hakim munawar; hanum fadhilah; Antonius Reuben (The ASEAN Journal of Military and Preventive Medicine, 2026)
Body composition significantly influences physical performance, including running ability. Muscle mass and fat mass are key factors in determining strength, endurance, and efficiency. This study analyzes the relationship between body composition and 12- minute running distance among cadet students in the Undergraduate Medical Program Cohort 4 at the Republic of Indonesia Defense University. This cross-sectional study measured body composition using bioelectrical impedance analysis (BIA) and assessed running performance through a 12-minute run test. Statistical analysis was conducted to evaluate the relationship between muscle mass, fat mass, and running distance. The study found a significant relationship between body composition and running performance. Male participants, with higher muscle mass and lower fat mass, outperformed females in average running distance and maximum distance achieved. Muscle mass and fat mass significantly affect 12-minute running performance, highlighting their importance in designing effective physical training programs. Further research is needed to explore additional factors influencing physical performance.